Glandula Tiroid Problem: Literature Review - Abdul Hafiz, Muhammad Zaki; Daan khambri (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Thyroid cancer is the most common endocrine system neoplasm.Based on the